Um pedacinho do céu em Moria: expressões simbólicas e estados emocionais nos desenhos de crianças e de adolescentes refugiados - Molina, Ana Carolina Segolin (2024)
Every year, countless people affected by adversities happening around the world dislocate themselves in search of a new place to live. In 2015, thousands crossed the Mediterranean and Aegean seas to seek refuge in Europe, and landed in Greece, where many were sheltered in the Moria Refugee Camp, where children and adolescents, who left their homes because they no longer felt safe living in them found, instead of a new home, an inhospitable place to live. They slept in crowded tents and survived with few resources, while waiting for unknown people to evaluate their requests for protection, and whether or not to grant them permission to remain in European soil. The objectives of this work were to identify and interpret the symbols present in the drawings produced by the children and the adolescents who lived in the Moria Refugee Camp and in its unofficial extension, called Olive Grove, in 2019, and to reflect on the emotional states of this population, during their experience in this context, using the theoretical framework of Analytical (Junguian) Psychology